Evaluating the Impact of Staff Cybersecurity Culture on Cyber Resilience in Colleges of Education: Insights from 12 Colleges of Education in Ghana - Daniel Paa Korsah (Journal of Education and Learning Technology)
Tertiary educational institutions have become increasingly reliant on computers and network technologies for their operations in the last few decades and this comes with a significant increase in cyber threats. Ghanaian Colleges of Education (CoEs), which are responsible for training teachers for basic schools, also face these cybersecurity challenges. A key solution to mitigating these challenges is the development of a robust cybersecurity culture among academic and non-academic staff. This study aimed to assess the impact of the Cybersecurity Act 2020 (Act 1038) on staff perceptions of the importance of cybersecurity, the effectiveness of technical measures against cyber threats and the perceived cyber resilience of the colleges. The study employed a mixed-method approach, using a descriptive cross-sectional survey design with a sample of 298 academic and non-academic staff from 12 colleges. A questionnaire and an interview guide were used to collect both quantitative and qualitative data. The findings revealed that awareness of the Cybersecurity Act 2020 was low among CoE staff, limiting its impact on their perception of cybersecurity importance. Despite low awareness of the Act, staff demonstrated a strong commitment to personal cybersecurity practices, indicating a need for structured institutional cybersecurity policies and training. The study emphasizes the need for targeted cybersecurity awareness programs for CoE staff and stronger collaboration between CoEs, the Ministry of Education and other stakeholders to establish a proactive cybersecurity culture. Empirical data on how staff in Ghanaian CoEs perceive and practice cybersecurity is presented, contributing to the expanding research on cybersecurity culture in educational institutions.